Copying Mechanisms in Repeated Floods Areas: A Case Study in Ba Baong Commune in Prey Veng Province, Cambodia - Ourn, Vimoil; Suntornvongsagul, Kallaya (Environment and Natural Resources Journal, 2015)
Vulnerable communities in Cambodia where annually experiences the repeated floods need the encouragement of their capacity mechanisms. The research study aimed to understand livelihoods of local communities experiencing repeated flooding and the building range of coping mechanisms of community based on available community resources which made the vulnerable people in the community to be able to increase their resiliency to the repeated floods in bigger scales. Approaching to the aims of study, Ba Baong commune in Prey Veng Province of Cambodia was selected for sources of information. Data collection was conducted regarding livelihoods of local people in the commune and flood patterns in relation to the coping mechanisms by document reviews, field observation, focus group discussion and interviews. The accumulated coping capacity was focused for the local management of community to minimize the flood damage at different flood stages; preparing, responding, recovering stages. The results revealed that their livelihoods were changed related with flood patterns: month starting rainy season, flood levels and flood duration. They adapted to the floods depending on utilization of available resources by the community achievement at various beneficial ends and important actions of local people adopted in order to remediate flood adverse impacts. Community capitals culturally shared among individuals by building trusts among local people in the community, motivation to work together, and self-reliance that were employed in Ba Baong community as immediate informal response to overcome hardships whereas the external supports were believed to be another crucial mechanism contributing effective flood responses. Therefore, that national policy should systematically learn the local coping capacities and mechanisms applied in a community level in order to promote the more effective informal and formal coping mechanism in a sustainable way.